2017
DOI: 10.1136/annrheumdis-2016-210775
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-induced remission in very early peripheral spondyloarthritis: the CRESPA study

Abstract: NCT01426815; Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 26 publications
1
35
0
2
Order By: Relevance
“…Proportion of patients achieving a status of clinical remission, major response, and nonresponse. The results of the first 24 weeks, a double‐blind placebo‐controlled phase, have already been reported . Forty‐nine of the 60 patients (82%) achieved the status of sustained clinical remission at week 48 (Figure A), the majority of whom had already achieved this status at week 24 (n = 30), with an additional 11 and 8 patients at weeks 36 and 48, respectively (Figure B).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Proportion of patients achieving a status of clinical remission, major response, and nonresponse. The results of the first 24 weeks, a double‐blind placebo‐controlled phase, have already been reported . Forty‐nine of the 60 patients (82%) achieved the status of sustained clinical remission at week 48 (Figure A), the majority of whom had already achieved this status at week 24 (n = 30), with an additional 11 and 8 patients at weeks 36 and 48, respectively (Figure B).…”
Section: Resultsmentioning
confidence: 82%
“…It corroborates and extends our earlier results that initiation of TNF blockade in very early peripheral SpA yields remarkably high rates of clinical remission. In contrast, substantially lower responses are observed in patients with more established forms of the disease . Importantly, the lack of a significant response in placebo‐treated patients ruled out the possibility of spontaneous remission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In einer großen doppelblinden randomisierten Placebo-kontrollierten Studie bei insgesamt 313 Patienten mit aktiver Psoriasis-Arthritis fand sich bei den 118 Patienten, die auch eine Enthesitis hatten, eine Verbesserung der Enthesitisregionen über zwei Jahre, erreichte aber nach 24 Wochen keine Signifikanz (56). In einer Studie mit Golimumab bei sehr früher peripherer SpA zeigte Golimumab gegenüber Placebo eine signifikante Überlegenheit bezüglich des Maastricht-Enthesitis-Scores (57).…”
Section: Mrtunclassified
“…However, the important limitation of this study was the open-label design and these data have not yet been confirmed in a placebo-controlled setting in PsA. Exploring the same concept in a slightly different population, Carron et al investigated the early initiation of TNFi treatment in a placebo-controlled study in a mixed population of patients with early peripheral spondyloarthritis, of which 40% had concomitant nail or skin psoriasis 19. Patients achieved clinical remission (defined as absence of arthritis, enthesitis and dactylitis) in 75% in the TNFi-treated arm versus 20% in the placebo arm.…”
Section: Introductionmentioning
confidence: 99%